Antioxidant activity, Total Phenolic and Flavonoid Contents and Cytotoxic activity of Euphorbia aegyptiaca - Osman Adam, Osman Adam; Abadi, Ragaa Satti Mohmmed; Ayoub, Saad Mohamed Hussein (Journal of Drug Delivery and Therapeutics, 2020)
Euphorbia aegyptiaca is a herbaceous plant traditionally used in Sudan for treatment of various diseases, and the study of this plant is still limited. The aim of the present study was to screen the phytochemicals and to assess the Antioxidant activity, total phenolic, flavonoid contents and cytotoxic activity of Euphorbia aegyptiaca. The plant material was extracted successively by Soxhlet apparatus using n-hexane, chloroform and methanol. The chemical constituents of the extracts were carried out using the standard procedures. The Folin- Ciocalteu and Aluminium chloride method was employed to calculate the total phenolic and flavonoid content, respectively. The antioxidant activity, was assessed by measuring the scavenging activity of the DPPH (2.2Di (4-tert-octylphenyl)-1-picryl-hydrazyl) and Propyl Gallate as standard antioxidants. While cytotoxic activities were screened using brine shrimp. Phytochemical screening studies revealed that flavonoids, tannins, coumarins, saponins, sterols, terpenes, anthraquinones and alkaloids were the main phytochemicals present in extracts of E. aegyptiaca. The methanol extract showed the highest level of total phenolic contents (173.49±2.427 mg GAE/g) and flavonoid content (239.53±7.90 mg QE/g), and the highest antioxidant activity 89% with least (IC50 0.0449µg/ml), and the no toxicity against brine shrimp (LD50 3423.156). Furthermore, no toxicity in all extracts was observed. The present study is the first evaluation regarding the characterization of E. aegyptiaca and its safety, and the results demonstrate its antioxidant potential and suggest its safe therapeutic use. The results suggest that methanol extract is a rich source of phytochemicals and exhibits highest amount of and total phenolic, flavonoid content and significant antioxidant activity and it has no cytotoxic activity. E. aegyptiaca plant can be regarded as a promising Source of naturally occurring potential antioxidants.Keywords: Euphorbia aegyptiaca, Sudan, Antioxidant, Total phenolic, total flavonoid, Cytotoxicity.